The Influence Of Sanitation, Hygiene And Menu Variations On Guest Satisfaction At Kapolagha Restaurant Hotel Grandhika Pemuda Semarang - Septiana Raihan Saputri; Krisnawati Setyaningrum; Mochamad Ainan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to determine and analyze the influence of sanitation, hygiene and menu variations on guest satisfaction at Kapolagha Restaurant, Grandhika Pemuda Hotel, Semarang. The research method used is a quantitative research method, where variables are measured using a Likert scale. The data collection method was carried out by distributing questionnaires to respondents. The population in this study were 100 guests at the Kapolagha Restaurant, Grandhika Pemuda Hotel, Semarang. Data processing uses SPSS tools, with descriptive analysis and multiple regression analysis hypothesis testing. The research results show that sanitation variables have a positive and significant effect on guest satisfaction; hygiene variables have a positive and significant effect on guest satisfaction; the menu variation variable has a positive and significant effect on guest satisfaction; sanitation, hygiene and menu variety variables have a positive and significant effect on guest satisfaction; and the menu variation variable is the most dominant variable in guest satisfaction.